The Relationship Between Body Image and Psychological Well-Being Among Female Adolescents - Rahma Rohadatulaisy; Destria Efliani; Rifa Yanti; Epu Margias Tuti (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Adolescent Female are vulnerable to body image issues due to physical changes and social pressures, which may affect psychological well-being. This study aimed to examine the relationship between body image and psychological well-being among adolescent girls at the Institute of Health and Technology Al Insyirah Pekanbaru. Method: A quantitative correlational study with a cross-sectional design was conducted involving 73 adolescent girls selected through purposive sampling. Body image was measured using the Multidimensional Body Self-Relation Questionnaire (MBSRQ), while psychological well-being was assessed using the 18-item Ryff Psychological Well-Being Scale. Data were analyzed using the Spearman rho correlation test. Result: The results showed a significant positive relationship between body image and psychological well-being (r = 0.410; p < 0.05). Conclusion: These findings indicate that adolescents with a more positive body image tend to have higher psychological well-being.